Penguatan Nilai Tanggung Jawab dan Disiplin Melalui Pembelajaran Kebersihan Diri Kelas 4 di MIS NWDI Dasan Lekong - Yani, Siti Rahma; Harni, Misni; Astuti, Linda Dwi; Zainiyah, Wahida; Putri, Devina Vinkkan Surya (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the strengthening of students' responsibility and discipline values through self-hygiene learning in grade 4 at MIS NWDI Dasan Lekong. The research method used is qualitative research. The study was conducted at MIS NWDI Dasan Lekong with the research subjects being grade IV A & B elementary school students totaling 29 children. Data sources were obtained from questionnaires or surveys for grades IV A & B. Data collection was conducted through 10 questionnaire/survey questions that had been prepared. Data analysis was carried out in three stages, namely data collection, data reduction, data verification, and data conclusion. Research results show that personal hygiene practiced in grade 4 at MIS NWDI Dasan Lekong significantly strengthens students' sense of responsibility and discipline. This program successfully habituates students to perform good personal hygiene behaviors, such as disposing of trash properly and washing hands regularly, which are tangible manifestations of responsibility towards oneself and the environment. Students' discipline also showed improvement through their consistency in following the hygiene routines taught during the learning program. This habit not only develops the physical aspects of cleanliness but also shapes moral character, including obedience and awareness of the importance of hygiene in supporting health and everyday quality of life.